2021
DOI: 10.7189/jogh.11.05013
|View full text |Cite
|
Sign up to set email alerts
|

Risk of infection and transmission of SARS-CoV-2 among children and adolescents in households, communities and educational settings: A systematic review and meta-analysis

Abstract: Background There is uncertainty with respect to SARS-CoV-2 transmission in children (0-19 years) with controversy on effectiveness of school-closures in controlling the pandemic. It is of equal importance to evaluate the risk of transmission in children who are often asymptomatic or mildly symptomatic carriers that may incidentally transmit SARS-CoV-2 in different settings. We conducted this review to assess transmission and risks for SARS-CoV-2 in children (by age-groups or grades) in community a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 118 publications
3
48
2
4
Order By: Relevance
“…2a). These findings indicate an age shift for delta variant, as the COVID-19 infections with the WT strains were not common in young, and development of severe symptoms and need of hospitalization was primarily limited to adult, more specifically in elderly 17,18 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…2a). These findings indicate an age shift for delta variant, as the COVID-19 infections with the WT strains were not common in young, and development of severe symptoms and need of hospitalization was primarily limited to adult, more specifically in elderly 17,18 .…”
Section: Discussionmentioning
confidence: 87%
“…2a). These findings indicate an age shift for delta variant, as the COVID-19 infections with the WT strains were not common in young, and development of severe symptoms and need of hospitalization was primarily limited to adult, more specifically in elderly 17,18 . Furthermore, we observed that, although, proportion of men was still higher than women for contracting infection (59% vs. 41%), a higher proportion of women contracted infection (41% vs. 36%) with delta variant.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This Special Issue has contextual relevance in light of the broad spectrum of direct and collateral effects wrought by the COVID-19 pandemic on social, economic, and health-related conditions [ 6 ]. These effects, direct and indirect, can be grouped broadly in relation to current controversies, such as the upsurge in direct infections among children and adolescents in the wake of the global spread of the B1.617.2 (Delta) variant [ 7 ], and the uncertain relationship of community spread with school closures and reopening [ 8 ]. Currently, the global inequity in COVID-19 vaccine availability and uptake as well as the debate on deferring vaccinations for children and adolescents in high-income countries (HICs) to vaccinate adults in LMICs, also pose major ethical dilemmas [ 9 ].…”
mentioning
confidence: 99%